2017
DOI: 10.1515/znb-2016-0222
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of the coordination behavior of a tetradentate NO3-donor amino alcohol ligand toward a CdII:HgII mixture

Abstract: Abstract:In this work, the reaction of 2,2′,2″-nitrilotriethanol (NTE) with a 1:1 mixture of CdI 2 and HgI 2 is investigated. The complex [Cd(NTE) 2 ][Hg 2 (μ-I) 2 I 4 ] was synthesized and identified by elemental analysis, FT-IR, 1 H NMR spectroscopy and single-crystal X-ray diffraction. The structure of the [HNTE]Cl salt is also presented. In the crystal structure of the complex, the cadmium atom has a CdN 2 O 6 environment in a slightly distorted cube geometry. This geometry is one of the rare cube geometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…9 ), respectively, confirming that 2 is more stabilized in the solid state by its network interactions than the others. 75 Also comparing the energy level of interactions for one molecule of 2 with the trapped methanol molecule in the crystal network of 2 showed that one molecule of 2 is more stabilized than the methanol molecule by inter molecular interactions. In 1, 89% of the total energy equates to the interactions with its fourteen closest neighboring molecules in ranges of 7.147–13.965 Å distances ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 ), respectively, confirming that 2 is more stabilized in the solid state by its network interactions than the others. 75 Also comparing the energy level of interactions for one molecule of 2 with the trapped methanol molecule in the crystal network of 2 showed that one molecule of 2 is more stabilized than the methanol molecule by inter molecular interactions. In 1, 89% of the total energy equates to the interactions with its fourteen closest neighboring molecules in ranges of 7.147–13.965 Å distances ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Total intermolecular interaction energy for one molecule of the complexes 1-3 were calculated using Mercury 73 and its CSD-materials tool. 62,74 For this, the sum of the intermolecular interactions energy in a molecular packing shell containing 100 molecules 75 around the one molecule of 1-3 were calculated to be À390.23, À561.05 (complex 2), À44.96 (MeOH in the 2) and À420.68 kJ mol À1 (Fig. 9), respectively, conrming that 2 is more stabilized in the solid state by its network interactions than the others.…”
Section: Description Of the Crystal Structuresmentioning
confidence: 99%
“…were calculated using Mercury [78] and its CSD-materials tool [79,80]. For this, the sum of the intermolecular interactions energy in a molecular packing shell containing 100 molecules [81] around the one molecule of 3 and Z-HMPP were calculated to be −997.12 (complex 3 containing Zn1B), −969.762 (complex 3 containing Zn1A) and -339.548 kJ/mol (Fig. 7), respectively, confirming that one molecule of complex 3 is more stabilized in the solid state by its network interactions than Z-HMPP [81].…”
Section: Total Intermolecular Interaction Energy 1 For One Molecule Omentioning
confidence: 99%
“…In the crystal packing of the 1, the O-H • • • I hydrogen bonds participate in the formation of one 4 (22) hydrogen bond motif[40,41].…”
mentioning
confidence: 99%